An introduction to the Planck mission. Issue 4 (2nd October 2017) - Clements, David L.
Abstract : The Cosmic Microwave Background (CMB) is the oldest light in the universe. It is seen today as black body radiation at a near-uniform temperature of 2.73 K covering the entire sky. This radiation field is not perfectly uniform, but includes within it temperature anisotropies of orderΔ T / T ∼ 10 - 5 . Physical processes in the early universe have left their fingerprints in these CMB anisotropies, which later grew to become the galaxies and large scale structure we see today. CMB anisotropy observations are thus a key tool for cosmology. The Planck mission was the European Space Agency's probe of the CMB. Its unique design allowed CMB anisotropies to be measured to greater precision over a wider range of scales than ever before. This article provides an introduction to the Planck mission, including its goals and motivation, its instrumentation and technology, the physics of the CMB, how the contaminating astrophysical foregrounds were overcome, and the key cosmological results that this mission has so far produced.